Secondary traumatic stress (compassion fatigue): a study in allied medical sciences - Durrant, Pamela June (My University, 2014)
This longitudinal research sought to investigate whether students (n=100) in the allied medical sciences of Physiotherapy (1997 and 1998 3rd year students) and Occupational Therapy (1998 3rd year students) are at risk of developing symptoms of compassion fatigue (which is identical to and presents in the same way as secondary traumatic stress disorder (STSD) and thus is the equivalent of PTSD). It also sought to investigate whether physiotherapy and occupational therapy students differ in the degree of risk and if a trend emerged within the groups that indicates that exposure to more traumatically injured types of patients contributes more to this risk than exposure to other patients. The study, in addition, investigated whether it is invariant that strong perceived social support reflects lower degrees of risk of compassion fatigue. The dependent variable of risk of compassion fatigue was captured by using the Compassion Fatigue Scale (CFS) developed by Figley (1995) while Joseph et al’s (1992) Crisis Support Questionnaire (CSQ) was used to measure the perceived social support variable. The psychometric properties of both the CFS and the CSQ were sound and supported the use of these instruments in the study. The statistical procedures used to analyse the data were simple descriptive statistics such as means, frequencies, standard deviatic-. i-tests, partial correlations. A number of open-ended questions were administered at r.g end of each questionnaire in order to illuminate the findings. Observations were measured, in this interrupted time series design, on seven different occasions during a 9 mouth period in 1997 and again in 1998 (physiotherapy students) and on four different occasions during 1998 (occupational therapy students) - overall 18 data collections and 597 questionnairs. The results indicate that the students are at risk of compassion fatigue (STSD), that there is no difference in the degree of risk between physiotherapy and occupational therapy students’ post patient exposure, and that there is a trend within both the 1997 and 1998 groups which indicates that exposure to the more traumatised patient contributes to this risk to a greater degree than does exposure to other patients. Although intuitively it was hypothesised that perceived social support may ameliorate the degree of risk of compassion fatigue (STSD) no significant consistency is found between the two. Some practical recommendations are suggested which may assist in reducing this risk in future physiotherapy and occupational therapy students. Some future research suggestions are also given.